Speciation of [Cp*2M2O5] in Polar and Donor Solvents1. Issue 12 (10th February 2013) - Sözen‐Aktaş, Pelin; Del Rosal, Iker; Manoury, Eric; Demirhan, Funda; Lledós, Agustí; Poli, Rinaldo
Abstract The speciation of compounds [Cp*2M2O5] (M=Mo, W; Cp*=pentamethylcyclopentadienyl) in different protic and aprotic polar solvents (methanol, dimethyl sulfoxide, acetone, acetonitrile), in the presence of variable amounts of water or acid/base, has been investigated by 1H NMR spectrometry and electrical conductivity. Specific hypotheses suggested by the experimental results have been further probed by DFT calculations. The solvent (S)‐assisted ionic dissociation to generate [Cp*MO2(S)]+ and [Cp*MO3]− takes place extensively for both metals only in water/methanol mixtures. Equilibrium amounts of the neutral hydroxido species [Cp*MO2(OH)] are generated in the presence of water, with the relative amount increasing in the order MeCN≈acetone<MeOH<DMSO. Addition of a base (Et3N) converts [Cp*2M2O5] into [Et3NH]+[Cp*MO3]−, for which the presence of a NH⋅⋅⋅OM interaction is revealed by 1H NMR spectroscopy in comparison with the sodium salts, Na+[Cp*MO3]−. These are fully dissociated in DMSO and MeOH, but display a slow equilibrium between free ions and the ion pair in MeCN and acetone. Only one resonance is observed for mixtures of [Cp*MO3]− and [Cp*MO2(OH)] because of a rapid self‐exchange. In the presence of extensive ionic dissociation, only one resonance is observed for mixtures of the cationic [Cp*MO2(S)]+ product and the residual undissociated [Cp*2M2O5] because of a rapid associative exchange via the trinuclear [Cp*3M3O7]+ intermediate. In neat methanol, complex [Cp*2W2O5] reacts to yield extensive amounts of a new species, formulated as the mononuclear methoxido complex [Cp*WO2(OMe)] on the basis of the DFT study. An equivalent product is not observed for the Mo system. The addition of increasing amounts of water results in the rapid decrease of this product in favor of [Cp*2W2O5] and [Cp*WO2(OH)].